2016
DOI: 10.1027/1864-1105/a000137
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Presence Experience Scale (SPES)

Abstract: Abstract. The study of spatial presence is currently receiving increased attention in both media psychology and communication research. The present paper introduces the Spatial Presence Experience Scale (SPES), a short eight-item self-report measure. The SPES is derived from a process model of spatial presence ( Wirth et al., 2007 , Media Psychology, 9, 493–525), and assesses spatial presence as a two-dimensional construct that comprises a user’s self-location and perceived possible actions in a media environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(107 citation statements)
references
References 64 publications
3
102
2
Order By: Relevance
“…Consistent with some of the previous literature, that makes use of desktop systems, differences in self-reported imagery ability were found to be related to spatial presence (e.g. Hartmann et al 2016). The better the reported imagery ability the more spatially present participants felt.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Consistent with some of the previous literature, that makes use of desktop systems, differences in self-reported imagery ability were found to be related to spatial presence (e.g. Hartmann et al 2016). The better the reported imagery ability the more spatially present participants felt.…”
Section: Discussionsupporting
confidence: 88%
“…The results were consistent across both scenarios indicating that they generalise across at least these two different experiences. That the relationships identified were also consistent with findings using desktop systems (Hartmann et al 2016) and the process model in general (Wirth et al 2007) adds further support to the possibility that the results reported here are unlikely to be environment specific. Instead, it appears to be the case that there is something special about selfreports of imagery and spatial presence which is distinct from at least some traditional tests of spatial ability.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations